2020
DOI: 10.3390/biomedicines8080249
|View full text |Cite
|
Sign up to set email alerts
|

Novel Bradykinin-Potentiating Peptides and Three-Finger Toxins from Viper Venom: Combined NGS Venom Gland Transcriptomics and Quantitative Venom Proteomics of the Azemiops feae Viper

Abstract: Feae’s viper Azemipos feae belongs to the Azemiopinae subfamily of the Viperidae family. The effects of Viperidae venoms are mostly coagulopathic with limited neurotoxicity manifested by phospholipases A2. From A. feae venom, we have earlier isolated azemiopsin, a novel neurotoxin inhibiting the nicotinic acetylcholine receptor. To characterize other A. feae toxins, we applied label-free quantitative proteomics, which revealed 120 unique proteins, the most abundant being serine proteinases and phospholipases A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 43 publications
0
11
2
Order By: Relevance
“…Each of these PLA 2 genes had transcript per million values >42,000 inferred using StringTie ( supplementary table S3, Supplementary Material online). This is in contrast to previous work that identified several PLA 2 isoforms, only a few of which were thought to be expressed in the venom gland ( Tsai et al 2016 ; Babenko et al 2020 ). It is possible that differences in the number of PLA 2 genes identified between these studies and here could reflect gene copy number polymorphism within A. feae .…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Each of these PLA 2 genes had transcript per million values >42,000 inferred using StringTie ( supplementary table S3, Supplementary Material online). This is in contrast to previous work that identified several PLA 2 isoforms, only a few of which were thought to be expressed in the venom gland ( Tsai et al 2016 ; Babenko et al 2020 ). It is possible that differences in the number of PLA 2 genes identified between these studies and here could reflect gene copy number polymorphism within A. feae .…”
Section: Resultscontrasting
confidence: 99%
“…2 A ). Previous studies have found that PLA 2 s are the most dominant toxin in Azemiops venom gland transcriptomes, however, the frequencies of other toxin components differ between our study and published Azemiops venom gland transcriptomes ( Babenko et al 2020 ). Variation in venom composition within populations and between species is commonly documented in snakes ( Schenberg 1959 ; Glenn and Straight 1989 ); additional sampling and studies are necessary to fully understand the variation present in Azemiops venom composition as well as the molecular mechanisms underlying this variation.…”
Section: Resultscontrasting
confidence: 95%
“…This finding, as well as the nearly complete absence of svMP and the high abundance of 3FTx (15%) is uncommon within venoms of this genus [ 77 ]. Even 3FTx have been extensively characterized from Elapidae, only few are described for Viperinae, like D. russelii and V. nikolskii , and the occurrence in such high amounts is considered as atypical and a rare toxin family in viper venoms [ 190 , 209 , 210 , 211 , 212 , 213 ].…”
Section: Venom Variations Of Old World Vipersmentioning
confidence: 99%
“…The BPPs R-BPP and Y-BPP, which we uncovered in the venom of the viper Azemiops feae ( Fig. 1 ) [ 26 ], are more similar to peptides exhibiting specificity for the ACE C domain and may be considered as a basis for the development of C domain-selective drugs, which would differ structurally from captopril.…”
Section: Snake Venoms: Composition and Propertiesmentioning
confidence: 99%